Individual student key performance using mobile web apps based on knowledge profile and cumulative grade point average - Aziah Khamis; Muhammad Suhaizan Sulong; Nur Ilyana Anwar Apandi; Azrita Alias (Institute of Advanced Engineering and Science, 2023)
This study investigated the performance of individual students toward the knowledge profile and cumulative grade point average or known as CGPA. The proposal of this paper involves two major components. The first component is investigating the individual student performance based on the knowledge profile and CGPA. The performance of students from cohort 2017 for the program Bachelor of Electrical Engineering (BEKG) courses in the Faculty of Electrical Engineering, Universiti Teknikal Malaysia Melaka (UTeM) was used as the dataset. The case study separates into various groups (excellent, honors and pass). Secondly, the study proposed a responsive web application leveraging a Google Visualization Feature to self-check individual academic performance. The goal of this app is to assist users in evaluating individual student performance and assist management in planning for continual quality improvement using the web and mobile apps. The marketing segments include students, academics, university, and school administration for analysis and evaluate the individual student’s performance.